Sintesis Hidroksiapatit dari Cangkang Kerang Darah dengan Variasi Waktu Sintering - Andriani Usman (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2026)
Hydroxyapatite (HAp) is a biomaterial widely used in medicine and tissue engineering due to its high biocompatibility and similarity to human bone minerals. Hydroxyapatite can be obtained from blood clam shells. This study aims to synthesise hydroxyapatite from blood clam shells. Blood clam shell powder was calcined at high temperatures to obtain calcium oxide (CaO), which was then reacted with a phosphate solution through a wet precipitation method to produce hydroxyapatite. The resulting product was characterised by FTIR, and the FTIR results showed the formation of functional groups that characterised the formation of hydroxyapatite namely the presence of OH- and PO43- functional groups.